A close shave? Performance of P2/N95 respirators in healthcare workers with facial hair: results of the BEARDS (BEnchmarking Adequate Respiratory DefenceS) study. Issue 4 (April 2020) - Sandaradura, I.; Goeman, E.; Pontivivo, G.; Fine, E.; Gray, H.; Kerr, S.; Marriott, D.; Harkness, J.; Andresen, D.
Summary: P2/N95 filtering face piece respirators (FFRs) protect healthcare workers (HCWs) from airborne infections. This study assessed the impact of facial hair on quantitative respirator fit in 105 male HCWs, of whom 38 were clean shaven, and assessed the prevalence of male facial hair at the study facility. Only 34 (32%) male HCWs overall achieved an adequate FFR fit, including 47% of clean-shaven men. No full-bearded HCWs achieved a fit. Adequate respirator fit decreased significantly with increasing facial hair ( P <0.01 for trend). Facial hair was present on 49% of male employees. This study supports quantitative fit testing prior to P2/N95 respirator use.